Epidemiological Characteristics and Formation Mechanisms of Multidrug-Resistant Hypervirulent Klebsiella pneumoniae - Tang, Miran; Kong, Xin; Hao, Jingchen; Liu, Jinbo (Frontiers in Microbiology, 2020)
Multi-drug resistance (MDR) and hypervirulence (hv) were exhibited by different well-separated Klebsiella pneumoniae lineages in the past, but their convergence clones—MDR-hypervirulent K. pneumoniae (HvKPs)—both highly pathogenic and resistant to most available antibiotics, have increasingly been reported. In light of the clonal lineages and molecular characteristics of the studied MDR-HvKP strains found in the literature since 2014, this review discusses the epidemiology of MDR-HvKPs, in particular summarizing the three general aspects of plasmids-associated mechanisms underlying the formation of MDR-HvKPs clones: MDR-classic K. pneumoniae (cKPs) acquiring hv plasmids, hvKPs obtaining MDR plasmids, and the acquisition of hybrid plasmids harboring virulence and resistance determinants. A deeper understanding of epidemiological characteristics and possible formation mechanisms of MDR-HvKPs is greatly needed for the proper surveillance and management of this potential threat.